Por que se Fazem as Festas? Breve Reflexão Sobre as Festas de Inverno no Concelho de Mogadouro - Neto, Antero (Trabalhos de Antropologia e Etnologia, 2020)
With this article I intend to perform a reflection about the meaning of the winter solstice rituals at Mogadouro region, in the northeast of Portugal, specifically about their impact in the little rural communities, and about the reason why they managed to survive until the present days and the importance of keeping these traditions alive.